2022
DOI: 10.1007/s11628-022-00479-8
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for travel insurance as a risk reduction behavior: health-related risk perception after the outbreak of COVID-19

Abstract: This study aims to identify the effects of health-related risk perception and sociodemographic characteristics on the willingness to pay (WTP) for travel insurance as a risk reduction behavior following the outbreak of COVID-19. Through the application of a double-bounded dichotomous choice contingent valuation method, this study found several determinants for travel insurance price (i.e., risk perception toward traveling, perception about the influence of COVID-19, past travel insurance purchase experience, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…HR and perceived HC are integral components that influence the attitude of Malaysian working adults toward travel insurance. The findings of hypothesis H 2 support the result reported by early scholars [e.g., ( 102 )], who found that HR had a positive influence on behavioral intention. They further indicated that the low-income index was associated with HR.…”
Section: Discussionsupporting
confidence: 89%
“…HR and perceived HC are integral components that influence the attitude of Malaysian working adults toward travel insurance. The findings of hypothesis H 2 support the result reported by early scholars [e.g., ( 102 )], who found that HR had a positive influence on behavioral intention. They further indicated that the low-income index was associated with HR.…”
Section: Discussionsupporting
confidence: 89%
“…COVID-19 has had a devastating effect on the hospitality industry, including hotels around the world [1][2][3][4][5]. Up to this point, studies linking the hospitality industry and COVID-19 have received a lot of academic attention [6].…”
Section: Introductionmentioning
confidence: 99%
“…Grzebieniak (2015) emphasises that by stating that "…in the process of building the trust and reputation, insurance companies must use not only traditional instruments of "public relations", but also much broader instruments defined as "client relations", i.e., the instruments of managing and protecting the relationships between an insurance institution and its most important clients. Therefore, it is reasonable to speak about the perception of service quality which is the result of comparison, i.e., what the client expects in relation to what he has received (Choe et al, 2022). An important element of proper service provision quality is the insurance awareness of customers of insurance institutions.…”
Section: Quality In Travel Insurancementioning
confidence: 99%